Features of the course dirofilariosis in the Zaporozhye region for the 2005-2014 years - Udoye, Edzhike Frank; Furyk, E. A.; Фурик, Олена Олександрівна (Запорізький державний медичний університет, 2015)
Dirofilariosis - rare in human transmissible worm infestation caused by the nematode D. repens, which is a parasite in the subcutaneous tissue of animals. A person is coincidental and host infection it is due to mosquito bites. The aim of the investigation- to study features of the course dirofilariosis in the Zaporozhye region for the 2005-2014 years.